Development and Application of a Validated LiquidChromatography-Mass Spectrometry Method fortheDetermination of Dexchlorpheniramine Maleate in Human Plasma: Determination of dexchlorpheniramine - Aravindaraj Joghee Raju; Gopinath Ram; Rajan Sekar; Mahesh Kumar Siddaiah; Nanjan Moola Joghee; Suresh Bhojraj (Iranian Journal of Pharmaceutical Sciences, 2007)
Aconvenient liquid chromatographic-single Quadrupole mass spectrometric(LC-MS) method was developed and validated for dexchlorpheniramine maleate (INNname: chlorphenamine) determination in human plasma. The need for just a singleliquid-liquid extraction with ethyl acetate and being highly sensitive were theadvantages of this method. The linearity was also excellent over the range of 1 to150 ng.ml-1of dexchlorpheniramine maleate concentration. The method wasstatistically validated for its selectivity, linearity, precision and robustness. This methodwas successfully applied to the analysis of chlorpheniramine maleate in clinicalstudies.